CD4-specific designed ankyrin repeat proteins are novel potent HIV entry inhibitors with unique characteristics. - Andreas Schweizer (Public Library of Science (PLoS), 2008)
Here, we describe the generation of a novel type of HIV entry inhibitor using the recently developed Designed Ankyrin Repeat Protein (DARPin) technology. DARPin proteins specific for human CD4 were selected from a DARPin DNA library using ribosome display. Selected pool members interacted specifically with CD4 and competed with gp120 for binding to CD4. DARPin proteins derived in the initial selection series inhibited HIV in a dose-dependent manner, but showed a relatively high variability in their capacity to block replication of patient isolates on primary CD4 T cells. In consequence, a second series of CD4-specific DARPins with improved affinity for CD4 was generated. These 2nd series DARPins potently inhibit infection of genetically divergent (subtype B and C) HIV isolates in the low nanomolar range, independent of coreceptor usage. Importantly, the actions of the CD4 binding DARPins were highly specific: no effect on cell viability or activation, CD4 memory cell function, or interference with CD4-independent virus entry was observed. These novel CD4 targeting molecules described here combine the unique characteristics of DARPins-high physical stability, specificity and low production costs-with the capacity to potently block HIV entry, rendering them promising candidates for microbicide development.